An Overview of Lignin & Hemicellulose Effect Upon Biodegradable Bamboo Fiber Composites Due to Moisture. (2017) - Banik, Nabanita; Dey, Vidyut; Sastry, G.R.K.
Abstract: Biodegradable green composites made from natural fibers offer a potential & commercial alternative to the petroleum based composite materials & also for various industrial & other applications where weight reduction is the primary criterion without compromising the strength, stiffness & wear resistance property. Two major oil crises (1973-134% & 1990-113% price hike) gave a sharpened awareness for the finite nature of fossil resources, a critical increase in the release of CO2 'greenhouse' gases into the atmosphere as a result of burning fossil resources & a drastic increase in the volume of waste has led the researchers to look for alternative materials to make the composites more eco-friendly which further necessitated the study of their properties. Continuous &accelerated depletion of petroleum also poses a threat to the availability of plastics & resin related products which ultimately results in loss of economic edge of composites over conventional materials. Inspite of their biodegradability & eco-friendly behaviour, the most influential factors that control the properties of the green composites are processing conditions, methodology, fiber/matrix interface & moisture absorption capability of natural fiber. Hence proper control of these factors can make the developed composite more efficient & flexible to different kinds of applications. This paper represents a comprehensive overview of the natural, green, eco-friendly bamboo fiber composite related problems due to the contact of humid condition & its extraction.